(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Murwani R, Sibero MT, Silitonga PRA, Ambariyanto A. 2021. Bioprospecting of cow’s ruminal microbiota from a slaughterhouse in Ambarawa, Central Java, Indonesia. Biodiversitas 22: 5030-5038. Ruminal microorganisms play essential roles in maintaining ruminant health. However, most studies focused only on ruminal lactic acid bacteria (LAB), although other ruminal microorganisms might have biological properties for biotechnological purposes. Therefore, the current study aimed to isolate ruminal bacteria (LAB and non-LAB) and fungi from ruminal material and conducted a bioprospecting study to understand their ability to produce antibacterial compounds and polysaccharide-degrading enzymes. The ruminal bacteria were isolated on MRS and ISP4 agar, while PDA was used to isolate the different fungi. The antibacterial property was tested against multidrug-resistant Escherichia coli and Salmonella enterica ser. Typhi. The ability to produce agarase, alginate-lyase, and carrageenase was screened. Prospective isolates were identified using DNA barcoding approach. Twelve bacteria were isolated using MRS agar, six from ISP4 agar, and four fungi from PDA. Among twelve bacteria from MRS agar, eleven were considered LAB, which consisted of Lactobacillus plantarum and Pediococcus acidilactici. Several classes of bacteria such as actinobacteria, firmicutes, ?-proteobacteria, and ?-proteobacteria were isolated during this study. In addition, three fungal classes, namely Saccharomycetes, Eurotiomycetes, and Mucoromycetes were also isolated. All bacteria from MRS agar were suggested to have potential compounds with antimicrobial activity, while all ruminal fungi exhibited potential sources of polysaccharide-degrading enzymes.